Increased homocysteine levels impair reference memory and reducecortical levels of acetylcholine in a mouse model of vascular cognitive impairment - Dam, Kevin; Füchtemeier, Martina; Farr, Tracy D.; Boehm-Sturm, Philipp; Foddis, Marco; Dirnagl, Ulrich; Malysheva, Olga; Jadavji, Nafisa M. (Elsevier, 2017)
Folates are B-vitamins that are vital for normal brain function. Deficiencies in folates either genetic(methylenetetrahydrofolate reductase, MTHFR) or dietary intake of folic acid result in elevated levelsof homocysteine. Clinical studies have shown that elevated levels of homocysteine (Hcy) may be associ-ated with the development of dementia, however this link remains unclear. The purpose of this study wasto evaluate the impact of increased Hcy levels on a mouse model of vascular cognitive impairment (VCI)produced by chronic hypoperfusion. Male and female Mthfr+/+and Mthfr+/−mice were placed on eithercontrol (CD) or folic acid deficient (FADD) diets after which all animals underwent microcoil implantationaround each common carotid artery or a sham procedure. Post-operatively animals were tested on theMorris water maze (MWM), y-maze, and rotarod. Animals had no motor impairments on the rotarod,y-maze, and could learn the location of the platform on the MWM. However, on day 8 of testing of MWMtesting during the probe trial, Mthfr+/−FADD microcoil mice spent significantly less time in the targetquadrant when compared to Mthfr+/−CD sham mice, suggesting impaired reference memory. All FADDmice had elevated levels of plasma homocysteine. MRI analysis revealed arterial remodeling was present in Mthfr+/− microcoil mice not Mthfr+/+ mice. Acetylcholine and related metabolites were reduced in cortical tissue because of microcoil implantation and elevated levels of homocysteine. Deficiencies in folate metabolism resulting in increased Hcy levels yield a metabolic profile that increases susceptibility to neurodegeneration in a mouse model of VCI.